2007
DOI: 10.1002/jmri.20995
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between MR and endothelial hyperplasia in low‐grade gliomas

Abstract: Purpose:To investigate the capacity of multimodal MR to detect endothelial hyperplasia (EH), which has been linked to the aggressiveness of gliomas and which is so far only detected by biopsy, an invasive technique that prevents repeated measurements and early detection. Materials and Methods:A total of 26 patients with lowgrade gliomas participated in the study. All underwent a histopathological analysis and a multimodal MR examination (spectroscopic, anatomic, diffusion, perfusion, and postcontrast imaging).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…MVCP in glial tumors has been attributed to exuberant proliferation of endothelial cells; however, the precise origin and composition of the cellular components contributing to MVCP remain unclear. CE has been shown to be correlate with MVD (29) as well as with endothelial hyperplasia (19) in gliomas. In the present study, CE regions showed statistically significant correlation with MVCP but not with MVD despite showing a positive trend.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…MVCP in glial tumors has been attributed to exuberant proliferation of endothelial cells; however, the precise origin and composition of the cellular components contributing to MVCP remain unclear. CE has been shown to be correlate with MVD (29) as well as with endothelial hyperplasia (19) in gliomas. In the present study, CE regions showed statistically significant correlation with MVCP but not with MVD despite showing a positive trend.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, MVCP (13,14), and VEGF expression (15)(16)(17) have been shown to correlate with tumor grade, aggressiveness, metastatic potential, and hence patient prognosis. These immunohistologic parameters have been shown to correlate with morphologic imaging features such as presence or absence of contrast enhancement as well as with various physiologic measures especially perfusion parameters (18)(19)(20).…”
mentioning
confidence: 98%
“…In addition, K trans , EnF and CBV have been identified as potentially grade independent prognosticators (22-25). The number of studies examining the relationship between DCE-MRI parameters and more specific histopathological features in glioma is currently small and predominantly focuses on vascular metrics such as blood volume and flow; however, significant correlations have been described between CBV and MVD (26-29), VEGF expression (27,30), cell density (29), endothelial proliferation (31) and mitotic activity (31) and between CBF and endothelial hyperplasia (32).…”
Section: Introductionmentioning
confidence: 99%
“…Both T1 and T2 values are determined by the molecular status of the water molecules in the tissue, and consequently, characterize the specific pathologic status of the tissue. Acute myocardial ischemia usually accompanies with prolongation of T1 and T2 values because of unbound water molecules after release of water from intracellular proteins 3-5). Intramyocardial hemorrhage induces oxidation of hemoglobin and produces methemoglobin after extravasation of red blood cells into the interstitium, which may cause T1 and T2 value fluctuation 6)…”
Section: Introductionmentioning
confidence: 99%